Hubungan Smartphone Addiction dan Stres Akademik dengan Prokrastinasi Akademik sebagai Mediator - Thifal Maida Wilhelmina; Aditya Dedy Nugraha (Jurnal Online Psikogenesis, 2025)
The increasing intensity of smartphone use among college students has the potential to affect academic workload and trigger maladaptive behavior. This study aims to analyze the role of academic procrastination as a mediator in the relationship between smartphone addiction and academic stress. This study used quantitative methods with a correlational design. The participants in this study consisted of 264 college students in the Special Region of Yogyakarta. The instruments used in this study included the Academic Stress Scale, the Smartphone Addiction Scale (SAS), and the Academic Procrastination Scale (APS). Data were analyzed using simple linear regression, multiple linear regression, and mediation analysis. The main findings indicate that smartphone addiction is significantly associated with academic stress, both directly (Direct = 0.307, 95% CI [0.179, 0.431], p < 0.001) and indirectly (Indirect = 0.224, 95% CI [0.144, 0.315], p < 0.001) through academic procrastination (Total = 0.531, 95% CI [0.415, 0.665], p < 0.001). This means that academic procrastination partially mediates the relationship between smartphone addiction and academic stress. This study highlights that increased smartphone addiction tends to elevate academic procrastination, which in turn leads to academic stress.